The effect of the different source of Bee-collected pollen ( Citrus , Anise ) on its chemical composition - نداف, محمد; سلطانة, علي; الضرف, ربى (Latakia University Journal -Biological Sciences Series, 2022)
The purpose of this study was to determine the physicochemical characteristics of pollen collected from Citrus and Anise in tow different seasons, the Citrus season for the year 2020, in the period between April and May in the coastal region (north of Lattakia), And the Anise season for the year 2020 in Al-Ghab area (Hama countryside). In both source, indoor traps were used to collect pollen samples. The main purpose for this study is, first, to know the effect of the different source of bee-collected pollen on its chemical composition in terms of its total sugar content ,Fructose, Glucose, Sacrose, Protein in addition to its Lipid and Ash content. The second, to study the effect of collecting areas climatic conditions on the pollen's chemical composition and the collecting process conditions standards. The results of this study are the following: the percentage of moisture decreased with a very high significance with an average 10.9% compared to the moisture content of Citrus pollen, which was on average 22.3% . This makes the process of collecting Anise pollen easier than that of Citrus, as high moisture content of Citrus pollen makes it spoil quickly. The protein content of anise pollen also increased with a very high significance it averaged 22.5% compared to 19.5% in Citrus. As for sugar, it was 56.24% , 41.57% for each of Anise and citrus respectively at level of significance of 5%.In addition to an increased level of Fructose, Glogose, Maltose in Anise pollen in very high significance compared to Citrus pollen. While the differences in the content of Proline and Ash between the two studied types were not significant.